(untitled) (Bangladesh Medical Journal, 2016)
Most children with congenital toxoplasmosis is an embryo foetopathy. It has been described all over congenital toxoplasmosis are developmentally normal1 but up to four percent die or have evidence of permanent neurological damage or bilateral visual impairment during the first years of age2,3 It is in this context that West syndrome can develop, and may be defined as a triad of menifestations infantile spasm and developmental delay and hypsrrythmic patern of EEG.4 Here this treatable and academic case, congenital toxoplasmosis & West syndrome was reported. Bangladesh Med J. 2014 Sep; 43 (3): 165-167